5(w+3)+3(3w+1)=14

Simple and best practice solution for 5(w+3)+3(3w+1)=14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(w+3)+3(3w+1)=14 equation:


Simplifying
5(w + 3) + 3(3w + 1) = 14

Reorder the terms:
5(3 + w) + 3(3w + 1) = 14
(3 * 5 + w * 5) + 3(3w + 1) = 14
(15 + 5w) + 3(3w + 1) = 14

Reorder the terms:
15 + 5w + 3(1 + 3w) = 14
15 + 5w + (1 * 3 + 3w * 3) = 14
15 + 5w + (3 + 9w) = 14

Reorder the terms:
15 + 3 + 5w + 9w = 14

Combine like terms: 15 + 3 = 18
18 + 5w + 9w = 14

Combine like terms: 5w + 9w = 14w
18 + 14w = 14

Solving
18 + 14w = 14

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-18' to each side of the equation.
18 + -18 + 14w = 14 + -18

Combine like terms: 18 + -18 = 0
0 + 14w = 14 + -18
14w = 14 + -18

Combine like terms: 14 + -18 = -4
14w = -4

Divide each side by '14'.
w = -0.2857142857

Simplifying
w = -0.2857142857

See similar equations:

| 5x+9=-5 | | -10(x-5)=100 | | .75x+.25(10-x)=.59(10) | | 3x-3=2x-9 | | 4x-10y=100 | | 2y+6y=48 | | 3(x+17)=5 | | -120=8x | | 2-3k=10 | | 6x+4+2x=42 | | -4z-7+12z=37-12 | | 6x+6=11x-24 | | 12-x=9 | | 6x+6=-34-4x | | 24=2m | | 2x+[x+3]=24 | | 33.7-(1.5s+2.3)=3.4-(0.4-5.7s) | | 5+4p=-7 | | 5x+4=x+20 | | -6z+4(z+3)=-2z+14 | | 6x+141=5x-3 | | XY+Y= | | -13+13=0 | | 5x-2(4+4x)=11 | | -4(4+7n)+5(3+4n)=-5n-2n | | a^4-7a^2+10=0 | | 9x-8=3x+4 | | 165+20x=180 | | -6n=2m+3 | | -4(4+7n)+5(3+4n)=-5-2n | | 15v-9v=42 | | y=-2(5)+2 |

Equations solver categories